Towards a SpatioTemporal Data Model for Traditional Ecological Knowledge/Indigenous Knowledge - Mackenzie, Kierin; Pirker, John; Reitsma, Femke (Cartographica, 2020)
Indigenous peoples have been making maps and utilizing GIS for some time, and have been mapped and cadastralized for some time as well. Models of Indigenous spatiality have been the topic of some work, but the data for modelling Indigenous spatiotemporality remain scant, and the subject matter is rich. This paper suggests another layer of representation for GIS when dealing with complex data with a strong relational and qualitative component. In this paper, we present a new data model that we are calling the spatiotemporal motif. It is an open data model incorporating choric (coordinate) as well as topic (attribute) space and chronic (coordinate) as well as kairic (attribute) time. The model aims to fill gaps in other data model depictions concerning lack of support for cyclical time, multiple constraints on what constitutes a proper time or place for a given activity, fluid and dynamic spatiotemporal boundaries, support for narratives and contingencies, and privacy and sensitivity concerns.